IMPACT OF LEARNING EARTH LITOSPHERE USING INTERACTIVE CONCEPTUAL INSTRUCTION ON LOGIC THINKING, CONCEPTUAL UNDERSTANDING, AND SPIRITUAL ASPECT EMBEDDING (Jurnal Pendidikan Fisika Indonesia, 2018)
The aim of this study is to explore the impact of interactive-conceptual-instruction with visualization on logic thinking, conceptual understanding and spiritual aspect embedding. The sampling technique used in this research was convenience sampling. This research used mixed methods with embedded experiment design. The data of logic thinking and conceptual understanding was collected through pre-test and post-test. The questionnaires were used to collect data on spiritual attitudes and were analyzed qualitatively. The results showed that logic thinking-ability improves from no logic thinking to inductive-deductive logic thinking. The improvement of logic thinking abilities was in the medium category. Understanding the concept shifted from incompetent to conceptual understanding with improvement, in the medium category. The questionnaires analysis showed that the students got spiritual values related to the awareness of God believing behind the natural phenomena that impact on their spiritual attitudes. This study also tried to apply the results of pure science research to support learning activities. Based on the result of the research, it can be concluded that the learning process using interactive conceptual with visualization can improve logic thinking, conceptual comprehension, and spiritual attitude embeding.